UPAYA MENINGKATKAN HASIL BELAJAR IPA MENGGUNAKAN PEMBELAJARAN KOOPERATIF TIPE JIGSAW SISWA KELAS IV SDN 163088 KOTA TEBING TINGGI - Isnayani Siregar (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2019)
The purpose of the study was to improve student learning outcomes in the material structure and function of plant parts of class IV 163088 Public Elementary School Jalan Nangka Tebing city using Jigsaw cooperative learning type. The subjects of this study were fourth grade students of SDN 163088 in Tebing Tinggi city, totaling 22 students. This study uses qualitative descriptive analysis techniques. Data analysis was collected through tests. Science using Jigsaw type cooperative learning can improve learning outcomes of class IV students at SD Negeri 163088 Tebingtinggi. This can be seen from the results of the tests obtained during the pre-cycle where the average score of the acquisition of students was 62.5 with classical completeness of 40.9%. After carrying out the first cycle and carried out the test at the end of the first cycle, there was an increase in students' understanding with the student average score of 74.3 and the classical completeness value of 72.7%. the test results obtained in the second cycle the average value of students is 80.22 with class completeness of 90.90%, hence this research is said to be successful. Keywords: learning outcomes, plant structure, Jigsaw